2006
DOI: 10.1098/rsbl.2006.0470
|View full text |Cite
|
Sign up to set email alerts
|

Oldest coelacanth, from the Early Devonian of Australia

Abstract: Coelacanths are well-known sarcopterygian (lobe-finned) fishes, which together with lungfishes are the closest extant relatives of land vertebrates (tetrapods). Coelacanths have both living representatives and a rich fossil record, but lack fossils older than the late Middle Devonian (385-390 Myr ago), conflicting with current phylogenies implying coelacanths diverged from other sarcopterygians in the earliest Devonian (410-415 Myr ago). Here, we report the discovery of a new coelacanth from the Early Devonian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…The presence of the dentary pore raises the tantalizing possibility that Eoactinistia may be an anatomically modern coelacanth, previously known only from the late Middle Devonian and younger age. However, the unknown phylogenetic position of Eoactinistia and the lack of any other Early Devonian coelacanth fossils make it impossible to weigh this possibility against other possibilities (that is, the dentary pore as an independently derived feature that arose twice among coelacanths, or as a primitive feature that was lost in other Devonian forms but then reappeared in later coelacanths) 17 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the dentary pore raises the tantalizing possibility that Eoactinistia may be an anatomically modern coelacanth, previously known only from the late Middle Devonian and younger age. However, the unknown phylogenetic position of Eoactinistia and the lack of any other Early Devonian coelacanth fossils make it impossible to weigh this possibility against other possibilities (that is, the dentary pore as an independently derived feature that arose twice among coelacanths, or as a primitive feature that was lost in other Devonian forms but then reappeared in later coelacanths) 17 .…”
mentioning
confidence: 99%
“…The early fossil record of coelacanths has been scarce, and opinions differ on which sarcopterygian taxon is the closest sister group of coelacanths 15,16 . So far, the earliest record of the traditionally defined coelacanth group 3,6,7,17 is one isolated dentary (Eoactinistia) from the Early Devonian (late Pragian, ~409 Myr ago) of Australia 17 . Because of its limited morphological features, Eoactinistia cannot be subjected to a phylogenetic analysis and its position within the coelacanths is unknown.…”
mentioning
confidence: 99%
“…The nearly unchanged morphology of coelacanths for the last 400 mya 4,13 has led to the conclusion that their behaviour, ecology and genetics are very likely unchanged since the Devonian, and several molecular studies have confirmed their slow rate of evolution at the genetic level [14][15][16][17] . However, recent population genetic studies revealed genetic divergence between individuals among and within the field sites and thus a potential for adaptation in L. chalumnae 18,19 .…”
mentioning
confidence: 99%
“…As this very first report from South Africa, more than a hundred individuals have been found off the East African Coast, most of them on the Comoros 2,3 . Researchers refer to coelacanths as 'living fossils' because of their nearly unchanged morphology since the late Devonian, approximately 400 mya ago 4 . They are of major scientific interest as they represent a very basal group of the gnathostomes.…”
mentioning
confidence: 99%
“…This group of lobe-finned fishes is presently represented by only two species found in the coastline of the Indian Ocean and Indonesia (Holder et al 1999), but in deep time they showed quite some diversity (Johanson et al 2006, Miguel et al 2014. Raphael Miguel (Universidade do Estado do Rio de Janeiro) and colleagues have reviewed the distribution of the extinct coelacanth group called Mawsoniidae.…”
mentioning
confidence: 99%